A study of life cycle assessment in two old neighbourhoods in Belgium. (January 2020) - Nematchoua, Modeste Kameni; Asadi, Somayeh; Reiter, Sigrid
Graphical abstract: Highlights: Energy consumption is 16% higher in urban than suburban neighbourhood. Eutrophication concentration is higher in the suburban area than urban. Demolition phase represents the 2.4% of total environmental impacts. Abstract: The aim of this research is to determine the most important source of environmental change at the two old neighbourhood. The study of multiple scenarios allows us to determine their Life Cycle Assessment (LCA) impacts and identify the key variables. The impact of storm water management, density, mobility, management of unoccupied space, and the use of renewable energies on the environmental balance sheet of two old neighbourhoods located in Urban and Suburban zones was quantified. The environmental data comes from several interviews with occupants, ECOINVENT database, developed by different research institutes based in Switzerland, and the U.S. Department of Energy's Office of Energy Efficiency and Renewable Energy which provides weather data for more than 2100 locations throughout the world. Three different software programs were used for studying the different environmental impacts. The results showed that the length of daily trips made by the residents, the presence of public transportation and bike path has no significant influence on the environment in the two old neighbourhoods. The variation of photochemical ozone is important in both neighbourhoods. However, the presence of water retention and distribution systems reduces up to 10% the environmental impacts and in particular eutrophication, waste production, acidification and damage to health.